Abdominal Pain After Pediatric Inflammatory Bowel Disease Diagnosis: Results From the ImproveCareNow Network. Issue 6 (December 2020) - Murphy, Lexa K.; Suskind, David L.; Qu, Pingping; Zhou, Chuan; Gashi, Kaltrina; Kawamura, Joy S.; Palermo, Tonya M.
ABSTRACT: Objectives: Although abdominal pain is a hallmark symptom of pediatric inflammatory bowel disease (IBD), limited research has examined pain during the first year after diagnosis. The purpose of the present study is to examine prevalence, predictors, and impact of abdominal pain during the 12 months after pediatric IBD diagnosis using data from the ImproveCareNow (ICN) Network. Patients and Methods: Participants consisted of 13, 875 youth (age 8–18 years, 44% female, 81% Caucasian) with IBD (65% Crohn's disease; 27% ulcerative colitis, 8% indeterminate colitis) enrolled in the ICN Network with data from clinic visits during the first year after diagnosis (1–22 visits; mean = 3.7). Multivariable mixed effects logistic regression models were conducted to analyze the presence versus the absence of abdominal pain, activity limitations, and decrements in well-being. Results: The percentage of youth reporting abdominal pain decreased significantly during the first year after diagnosis and yet a sizeable group reported continued pain at 12 months (55.9% at diagnosis; 34.0% at 12 months). Multivariable analyses revealed that greater time since diagnosis (odds ratio [OR] = 0.98, P < 0.001), higher disease severity (OR = 11.84, P < 0.001), presence of psychosocial risk factors (OR = 2.33, P = 0.036), and female sex (OR = 1.90, P < 0.010) were significant correlates of continuing abdominal pain. Abdominal pain was significantly associated with decrements in well-being (OR = 5.11, P < 0.001) as well as limitations in activity (OR = 9.31, P < 0.001), over and above the influence of disease severity. Conclusions: Abdominal pain is prevalent and impactful, even when controlling for disease activity, during the first year after pediatric IBD diagnosis. Results from the present study can inform screening and tailored pain management intervention efforts in pediatric IBD. Abstract : Supplemental Digital Content is available in the text